The phenomenon of philosophy in Afrikaans: On Pieter Duvenage’s Afrikaanse filosofie: Perspektiewe en dialoë - Louw, Dirk (Stellenbosch Theological Journal, 2018)
The year 2016 saw the publication of Afrikaanse filosofie: Perspektiewe en dialoë (“Afrikaanse” Philosophy: Perspectives and Dialogues) (Bloemfontein: SUN Press, ISBN: 9781920382780) by Pieter Duvenage, an attempt to trace the development over the last 100 years (apparently) of philosophy practised in the Afrikaans language. Duvenage is not the first to map the history of this philosophy, but he is the first to do so through engaging in dialogue with the philosophers in question (and not simply through writing about them) and through focusing specifically on its development at a number of mainly Afrikaans universities. I elaborate on the strengths and weaknesses of Duvenage’s book and end by exploring the sense in which “Afrikaanse” philosophy qualifies as “African” philosophy (an issue Duvenage neglects), thus becoming, not a target of decolonization and Africanization, but a vehicle thereof.